2019
DOI: 10.1007/s00265-019-2672-1
|View full text |Cite
|
Sign up to set email alerts
|

Nest-site defence aggression during courtship does not predict nestling provisioning in male collared flycatchers

Abstract: Individuals of many animal species show consistent differences in ecologically relevant behaviours, and these individual-specific behaviours can correlate with each other. In passerines, aggression during nest-site defence is one of those behaviours that have been steadily found to be repeatable within individuals. Furthermore, in several cases, aggression was related to some estimates of reproductive investment. Here, we studied the possibility that behaviour of males toward a male rival predicts the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Results of our experiment indicate that differences in inherently stable state variables (size, hind limb length) affect individual antipredator aggression, further emphasising the ecological and evolutionary relevance of this behaviour. Nevertheless, as other inherently labile traits, such as levels of testosterone are proved to substantially affect intraspecific social aggression in a various of taxa (Veiga et al 1998;Weiss and Moore 2004;O'Connor et al 2014;Szász et al 2019), further studies are needed to reveal potential background mechanisms behind variation in antipredator aggression. Linking antipredator-and social aggression in a behavioural syndrome framework (Sih et al 2004;Dingemanse et al 2012;Dochtermann and Dingemanse 2013), as well as understanding the inheritance of antipredator aggression also warrants future studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of our experiment indicate that differences in inherently stable state variables (size, hind limb length) affect individual antipredator aggression, further emphasising the ecological and evolutionary relevance of this behaviour. Nevertheless, as other inherently labile traits, such as levels of testosterone are proved to substantially affect intraspecific social aggression in a various of taxa (Veiga et al 1998;Weiss and Moore 2004;O'Connor et al 2014;Szász et al 2019), further studies are needed to reveal potential background mechanisms behind variation in antipredator aggression. Linking antipredator-and social aggression in a behavioural syndrome framework (Sih et al 2004;Dingemanse et al 2012;Dochtermann and Dingemanse 2013), as well as understanding the inheritance of antipredator aggression also warrants future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionary behavioural ecology of consistent individual behavioural differences across time and ecological situations in a population (i.e. animal personality) became intensively studied during the last decades (for reviews and meta-Communicated by S. Joy Downes analyses see Réale et al 2007;Sih and Bell 2008;Bell et al 2009;Sih et al 2012;Garamszegi et al 2013;Niemelä and Dingemanse 2018), and aggression is among the most frequently studied behavioural traits in this field across several taxa (Mafli et al 2011;Sih et al 2015;Santostefano et al 2016;Michelangeli et al 2017;Szász et al 2019). However, aggression is usually evaluated in a social context, where it is motivated by resource control, including territorial and dominance disputes (often termed 'offensive aggression'; see Nelson 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This can also be judged from their behavioral responses, as when returned to their territory focal males immediately started to display their nest-box for female stimuli, or displayed aggressive approaches toward the cage of the male stimuli ( Garamszegi et al 2008 ). In previous studies, we measured the latency to initiate an aggressive approach toward the male stimulus, but we found that this behavioral variable was weakly, if any, predicted by the identity of the stimulus ( Szász et al 2019 ). We did not make song recordings during the presentation of the stimuli, as focal males did not typically sing in these situations (they may have uttered some stereotyped contact calls when presented with female stimulus, but these have very little among-individual variance and different function than that of bird song used as a signal in sexual selection).…”
Section: Methodsmentioning
confidence: 96%
“…For detailed methods and results, see Laczi et al., 2017 . Additionally, for another experiment, video recordings were conducted (with 2‐hr footages) at other nests too with 10‐day‐‐old offspring ( n = 17 in 2015, n = 19 in 2016, see details in Szász et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%